Sosialisasi Pencegahan Stunting Berbasis Komunitas dalam Program Kuliah Kerja Nyata (KKN) di Desa Tamangede Kecamatan Gemuh - Darajah, Nely Irnik; Amalia, Tutut Afiatul; Irawan, Moh Bayu; Maslichah, Dewi Ayu; Maghfiroh, Niswatul; Kristiyani, Kristiyani; Kharisudin, Kharisudin; Khumaidillah, Ahmad; Musthofa, Hanif; Alif, Daroja; Khusna, Sinta Maulida; Maulana, M. Nabil Hadani; Alaya, Miftahul; Amalia, Vina (LPPM Sekolah Tinggi Islam Kendal, 2026)
Stunting is a public health problem caused by chronic malnutrition in children, which affects physical growth, cognitive development, and the quality of human resources in the future. Efforts to prevent stunting require a community-based approach that actively involves local communities. This study aims to describe the implementation of a community-based stunting prevention socialization program through the Community Service Program (Kuliah Kerja Nyata/KKN) in Tamangede Village, Gemuh District, Kendal Regency. The method used was a community service activity with an educational and participatory approach conducted through three stages: preparation, implementation, and evaluation. The activity was held on January 20, 2026, at the Tamangede Village Hall and involved 35 participants consisting of mothers with toddlers and Posyandu cadres. The socialization materials included the importance of the first 1,000 days of life (HPK), balanced nutrition, appropriate parenting practices, and a demonstration of supplementary feeding (PMT) using local food ingredients. The results showed that participants demonstrated high enthusiasm during the socialization and interactive discussion sessions. The evaluation indicated an increase in community understanding regarding the causes, impacts, and prevention strategies of stunting. Furthermore, the supplementary feeding demonstration provided practical knowledge that children’s nutritional needs can be fulfilled using easily accessible local food sources. In conclusion, community-based stunting prevention socialization through the KKN program can increase public knowledge and awareness about the importance of early stunting prevention. A participatory and contextual educational approach is proven to be effective in building collective awareness and strengthening the role of Posyandu cadres and families in sustainable stunting prevention efforts at the village level.